2020
DOI: 10.1007/s12630-020-01810-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an intensive care unit family education intervention on delirium knowledge: a pre-test post-test quasi-experimental study

Abstract: Purpose To create, validate, and refine an intensive care unit (ICU) delirium education intervention to prepare family members to partner with the ICU care team to detect delirium symptoms and prevent and manage delirium using nonpharmacological strategies. Methods In this pre-test post-test quasi-experimental study, consecutive eligible family members of critically ill patients admitted to an ICU completed an ICU Family Education Delirium intervention in two parts: 1) six-minute video on ICU delirium (risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
9
1
2
Order By: Relevance
“…Future work is needed to find out how these interventions impact delirium management and reduce incidence, length, and severity of ICU delirium. 22 Interestingly, within our study we found that one patient and their partner did not agree with the clinician's ICU delirium diagnosis. This was only mentioned in the interview once, but it would have been interesting to explore this contradicting finding.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Future work is needed to find out how these interventions impact delirium management and reduce incidence, length, and severity of ICU delirium. 22 Interestingly, within our study we found that one patient and their partner did not agree with the clinician's ICU delirium diagnosis. This was only mentioned in the interview once, but it would have been interesting to explore this contradicting finding.…”
Section: Discussioncontrasting
confidence: 59%
“…Future work is needed to find out how these interventions impact delirium management and reduce incidence, length, and severity of ICU delirium. 22…”
Section: Discussionmentioning
confidence: 99%
“…En relación a los conocimientos, tanto la capacitación presencial de pacientes de ACV (20) como los videos en cuidadores de pacientes con asma (15) , niños con epilepsia (16) y pacientes en cuidados intensivos (17) , han incrementado los conocimientos sobre la patología, condición de salud, o manejo, a pesar que para la evaluación de los conocimientos se haya usado adaptaciones de cuestionarios validados, cuestionarios validados, o cuestionarios desarrollados para la investigación sin un proceso de validación formal. En algunos estudios no se han considerado el nivel de instrucción de los cuidadores, y en otros, al igual que en éste, se ha encontrado que la mayoría de cuidadores tenían al menos el nivel secun-dario.…”
Section: Discussionunclassified
“…Los videos dirigidos a pacientes con enfermedad pulmonar obstructiva crónica (EPOC) han mejorado el conocimiento y la técnica en el uso de inhaladores (13) . De igual forma, los videos han aumentado los conocimientos de pacientes con ACV (14) , cuidadores de pacientes con asma (15) , niños con epilepsia (16) y pacientes en unidades de cuidados intensivos (17) . Por otro lado, el entrenamiento presencial entre los mismos cuidadores o con actores que hacen de pacientes, sumado a retroalimentación por parte del profesional de salud, han incrementado el conocimiento y autocompetencia de cuidadores de pacientes con demencia (18) , y la autoeficacia y preparación para el cuidado de los cuidadores de pacientes con cáncer (19) , de igual manera, los conocimientos y prácticas reportadas en cuidadores de pacientes con ACV (20) .…”
Section: Mensajes Clave Introducciónunclassified
“…definition, type, risk factors, symptoms, treatment, prevention, differentiation from other diseases, coping strategies, communication skills, prognosis and the role of the family caregiver) from nurses or researchers through educational interventions (Black et al, 2011; Boltz et al, 2014; Bull et al, 2017; Eghbali‐Babadi et al, 2017; Hwang & Kim, 2021; Keyser et al, 2012; Krewulak et al, 2020; Martinez et al, 2012; Rosenbloom & Fick, 2014). Family caregivers practised handling delirium by reviewing delirium case episodes (Bull et al, 2017; Krewulak et al, 2020; Rosenbloom & Fick, 2014). Education was administered one or more times for 10 min to 2 h depending on the location and method of education (Eghbali‐Babadi et al, 2017; Keyser et al, 2012; Martinez et al, 2012; Rosenbloom & Fick, 2014).…”
Section: Resultsmentioning
confidence: 99%